2005
DOI: 10.1051/lait:2005036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic headspace methods used for the analysis of the volatile composition of Spanish PDO ewe’s raw milk cheeses

Abstract: -Different dynamic headspace (DHS) methods used for determination of volatile compounds in cheeses were compared. Three different laboratories using gas chromatography coupled to mass spectrometry carried out the analyses of volatile compounds of Spanish Protected Designation of Origin ewe's raw milk cheeses. One laboratory used "purge and trap" (P&T) with thermal desorption of the trap by ultrafast microwave heating (MWH) and the other two laboratories used P&T with thermal desorption of the trap by resistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Analyzing the variables responsible for this separation, it may be seen that this difference is due to the fact that the samples take higher values in ethanol, ethyl acetate, acetaldehyde and 2-butanol, together with lower values in 2-heptanone, 2-pentanone, isopropanol, 2-pentanol, acetone and 2-heptanol. This result is in agreement with previous works indicating that ethanol is present at higher concentrations in cow's cheese than in sheep's cheese (Molina et al, 1999), while acetaldehyde is not one of the more important aldehydes in sheep's cheese (Barron, et al, 2005b;Fernández-García et al, 2004a, b) and it could not be found in goat's cheese (Castillo et al, 2007).…”
Section: Resultssupporting
confidence: 93%
“…Analyzing the variables responsible for this separation, it may be seen that this difference is due to the fact that the samples take higher values in ethanol, ethyl acetate, acetaldehyde and 2-butanol, together with lower values in 2-heptanone, 2-pentanone, isopropanol, 2-pentanol, acetone and 2-heptanol. This result is in agreement with previous works indicating that ethanol is present at higher concentrations in cow's cheese than in sheep's cheese (Molina et al, 1999), while acetaldehyde is not one of the more important aldehydes in sheep's cheese (Barron, et al, 2005b;Fernández-García et al, 2004a, b) and it could not be found in goat's cheese (Castillo et al, 2007).…”
Section: Resultssupporting
confidence: 93%
“…The volatile profile of ND cheeses, along with their above mentioned sensory characteristics, was concordant with results previously reported on Idiazabal cheese variety [5,14]. Acids were the most abundant chemical family in ND cheeses mainly due to the content of straight short-chain free fatty acids (FFA), in particular n-butanoic, n-hexanoic and n-octanoic (Table 2).…”
Section: Volatile Profile Of Non-defective Cheesessupporting
confidence: 89%
“…Some studies have associated these straight volatile acids with desirable and characteristic acid, pungent and rennet flavours of particular cheese varieties [5,12,[30][31][32][33]. So, the highest relative abundance of straight acids mostly contributed to the desirable flavours slightly acid, pungent and natural rennet in ND cheeses.…”
Section: Volatile Profile Of Non-defective Cheesesmentioning
confidence: 99%
“…As far as sample 1 composition is concerned, wherein acetoin was one of the main components, decanoic acid was not detected. In this regard, high amounts of acetoin have also been determined, especially in industrial Manchego cheese by using different extraction techniques (Barron et al 2005;Soto-Yarritu et al 2007;Poveda et al 2008). It may be due to the action of commercial starters containing Lactococcus lactis subsp.…”
Section: Influence Of Irradiation On Selected Volatile Constituents Imentioning
confidence: 99%